Gums and stabilisers for the food industry 14 - Williams, Peter A.; Phillips, Glyn O. (Special publication (Royal Society of Chemistry (Great Britain)), 2008)
A useful information source for researchers and other professionals in industry and academia, particularly those involved directly with food science.